Macário e La cruz del diablo: a caracterização da figura do diabo na literatura fantástica - Bergantini, Nathália Hernandes [UNESP] (2015)
This Masters dissertation called Macário e La cruz del diablo: the figure of the devil's characterization in fantastic literature, discourses about the way as the figure of the devil sets in two Álvares de Azevedo and Gustavo Adolfo Becker 's literary works, respectively. To study these two literay works and find similarities and differences between them, it will be study the figure of the devil, a creature widely used in literary works, especially in fantastic literay works; fantastic literary genre, because both literay works have features which allow insert them in fantastic literay genre. It will be also studied some features of Romanticism, whereas the two literary works studied here, were written during the romantic period. Other theories such as the tale, the theater, the legend and the comparative literature, will be briefly included when necessary, for the analysis of the literay works